Impacts of climate change on the suitable habitat of Angelica sinensis and analysis of its drivers in China - Shaoyang Xi; Xudong Guo; Xiaohui Ma; Ling Jin (Scientific Reports)
Abstract Climate change is shifting optimal habitats for medicinal plants, potentially compromising the efficacy and therapeutic value of herbal remedies. Global warming and increased extreme weather events threaten the sustainability and pharmaceutical integrity of Angelica sinensis (Oliv.) Diels (A. sinensis). Despite its importance in traditional herbal medicine, there is limited research on adaptation of A. sinensis to climate challenges. This study systematically collected occurrence data of A. sinensis through field expeditions and online databases, using the Maxent ecological niche modeling tool and ArcGIS software to forecast suitable habitats. A total of 402 species occurrence points and 21 environmental variables were selected for modeling, resulting in 1,160 distribution models, of which only one met the stringent 5% odds ratio (OR) standard. The optimal model exhibited a pROC value of 0, an OR of 0.0196, and an AICc score of 9,287.133. The model, run ten times for robustness, showed an average AUC of 0.980, indicating high accuracy and reliability. Under current climate conditions, suitable habitats for A. sinensis cover approximately 13% of mainland China, primarily in Gansu (73.77%), Qinghai (14.73%), and Sichuan (11.18%) provinces. Environmental factors such as altitude, humidity, and temperature significantly influence the geographical distribution of A. sinensis. The future climate scenario predictions suggest that suitable habitats will generally shift towards higher latitudes, with areas of moderate to high suitability primarily distributed across the provinces of Gansu and Qinghai. The interactions between environmental factors, characterized by mutual and nonlinear enhancement, further influence the spatial differentiation of suitability zones. Overlay analysis with 2020 land cover data indicated that 861,437 km² of arable and forest land are suitable for A. sinensis cultivation. Future predictions under four SSP scenarios show varying changes in suitable habitat areas, with the most significant expansion under SSP370 between 2080 and 2100, covering 14.54% of mainland China. These findings provide critical insights for optimizing A. sinensis cultivation regions and quality assessments in response to climate change.